Niban protein regulates apoptosis in HK-2 cells via caspase-dependent pathway - Shiqi Tang; Jianwen Wang; Jishi Liu; Yan Huang; Yueyi Zhou; Shikun Yang; Wei Zhang; Minghui Yang; Hao Zhang (Renal Failure, 2019)
Purpose: To investigate whether Niban protein plays a role in renal interstitial fibrosis by regulating renal tubular epithelial cell apoptosis and explore the underlying mechanism. Methods: Unilateral ureteral obstruction (UUO) model was performed in C57B/6J mice, and divided into sham operation group and groups of days 3, days 7, and days 14. Niban expression was detected by immunohistochemistry and Western blot. TUNEL assays were used to detected apoptosis. Niban siRNA and overexpression Niban plasmid were transfected in HK-2 cells respectively to explore apoptosis related mechanisms of Niban during angiotensin II (AngII) – and endoplasmic reticulum (ER) stress-induced injury. Results: With the development of obstruction, Niban’s expression decreased gradually while apoptosis increased. Silencing of Niban not only increased the AngII- and ER stress-induced apoptosis, but also promoted the expression of caspase 8, caspase 9, Bip, and Chop. Overexpression of Niban reduced AngII-induced apoptosis and the expression of caspase 8 and caspase 9. Conclusions: Niban protein is involved in apoptosis regulation in HK-2 cells, and most likely via caspase-dependent pathway.